BacSJ—Another Bacteriocin with Distinct Spectrum of Activity that Targets Man-PTS - Tymoszewska, Aleksandra (Int J Mol Sci, 2020)
Lactic acid bacteria produce diverse antimicrobial peptides called bacteriocins. Most bacteriocins target sensitive bacteria by binding to specific receptors. Although a plethora of bacteriocins have been identified, for only a few of them the receptors they recognize are known. Here, we identified permease IIC and surface protein IID, two membrane subunits of the mannose-specific quaternary phosphotransferase system (Man-PTS), as a receptor for BacSJ, a subclass IId bacteriocin produced by Lactobacillus paracasei subsp. paracasei BGSJ2-8. BacSJ shares 45% identity with another Man-PTS binding bacteriocin, garvicin Q (GarQ). Similarly to GarQ, BacSJ has a relatively broad activity spectrum acting against several Gram-positive bacteria, such as Lactococcus lactis and Listeria monocytogenes, harboring fairly similar Man-PTSs, but not against Lactococcus garvieae. To identify specific Man-PTS amino acids responsible for the L. lactis sensitivity to BacSJ, and thus likely involved in the interaction with this bacteriocin, we generated eight independent BacSJ resistant L. lactis mutants harboring five distinct missense mutations in the ptnC or ptnD genes encoding the IIC and IID subunits. Concurrently with the resistance to BacSJ, the mutants efficiently utilized mannose as a carbon source, which indicated functionality of their mutated Man-PTS. The amino acid substitutions in the mutants localized to the intracellular region of the IIC permease or to the extracellular parts of IID. This localization coincides with regions targeted by GarQ and some other Man-PTS-binding garvicins, pointing to similarities between all these bacteriocins in the mechanism of their interaction with Man-PTS. During the attack by these bacteriocins, subunits IID and IIC are assumed to function sequentially as a docking and an entry module allowing the toxic peptide to bind the cell and then open the pore. However, since not all of the BacSJ-resistant mutants exhibited cross-resistance to GarQ, we propose that BacSJ interacts with Man-PTS in a manner slightly different from that of GarQ.